Polarized Raman spectroscopy for studying two-dimensional materials - Kim, Jungcheol; Lee, Jae Ung; Cheong, Hyeonsik (Journal of Physics Condensed Matter, 2020)
Raman spectroscopy has been established as one of the core experimental tools to study two-dimensional materials (2DMs) including graphene, black phosphorus, transitional metal chalcogenides, and other layered materials. If the polarization of the incident photons and the scattered photons are carefully controlled, the selection rules for the Raman scattering from phonon modes allow accurate mode assignments, which is not always possible in Raman scattering measurements using unpolarized light. Furthermore, polarized Raman spectroscopy can be used to determine the crystallographic orientation of isotropic 2DMs with in-plane strain or anisotropic 2DMs. This review explains the basics of polarized Raman spectroscopy, especially in the context of 2DMs research, and survey some of the most important applications of polarized Raman spectroscopy in isotropic and anisotropic 2DMs studies.
Keywords: Crystallographic orientations; Layered material; Polarized raman spectroscopy; Raman Scattering measurements; Scattered photons; Transitional metals; Two-dimensional materials; Unpolarized light; graphene; polarization; Raman; two-dimensional material